ANALISIS YURIDIS PENANGANAN TINDAK PIDANA PENCUCIAN UANG YANG BERASAL DARI PENYELUNDUPAN DI INDONESIA - Semmi Kawulur, Denni; Timomor, Adensi; Engeline Pijoh, Feibe (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
Money Laundering (TPPU) is a serious crime with broad impacts on economic and social stability, and it is often linked to other offenses such as smuggling. This study aims to examine the legal handling of money laundering derived from smuggling activities, identify the obstacles in its enforcement, and provide recommendations to enhance the effectiveness of law enforcement in Indonesia. Using a normative legal research method, the study finds that addressing money laundering requires adaptive regulations and cross-sector collaboration, as this crime is increasingly complex, transnational, and frequently associated with organized crime. Synergy among regulations, law enforcement institutions, financial entities, technology, and public awareness is crucial to dismantle criminal networks and safeguard the integrity of the financial system.